NxGen evidence: Redesigning the Agency for Healthcare Research and Quality Effective Health Care website to promote engagement, interactivity, and usability of systematic reviews. (20th August 2020) - Reid, Edwin; Guise, Jeanne‐Marie; Fiordalisi, Celia; Macdonald, Scott; Chang, Stephanie
Abstract : Evidence‐based decision‐making is predicated on the ability of users to find and comprehend results from systematic review. Evidence producers have an obligation to support evidence users in this process. The Agency for Healthcare Research and Quality (AHRQ) Evidence‐based Practice Center (EPC) program—a producer of rigorous and comprehensive systematic reviews for two decades—has set a gold standard for reliability in health evidence reviews in the United States. It has recently begun a program of active support for evidence dissemination and uptake beyond mere publication of lengthy reports. This Brief Methods Note critiques the current paper‐based format for systematic reviews and describes the development of a next generation (NxGen) AHRQ EPC Effective Health Care website. This redesigned platform will allow end‐users of all types to find and share the evidence they need through data visualizations and other interactive displays. Several design principles guided the development of NxGen to make systematic review findings more accessible, customizable, adaptable, interactive, and shareable. NxGen will include visualizations for report results that are expressed as meta‐analyses as well as those with narrative syntheses, through forest or bubble plots, respectively. Visual and interactive evidence heat maps are also planned. The NxGen version of the Effective Health Care website is planned to go live in the latter half of 2020 or early 2021.